Atmospheric boundary layer dynamics and aerosol properties based on observations of unmanned research aircraft ... - Harm-Altstädter, Barbara (Niedersächsisches Forschungszentrum für Luftfahrt, 2022)
The outline of the thesis considers a characterization of dynamic processes and aerosol particles that were studied with unmanned aerial systems (UAS) in the atmospheric boundary layer (ABL) at two investigation areas; in the polar region and at a continental site in Middle Europe. The use of UAS provides a detailed 4-D picture of ABL properties, thus offers a high potential for filling the sparse small-scale observations that exist in the ABLdue to missing measurement tools. The Carolo T200 ”M2AV” (Mini Meteorological Aerial Vehicle) was applied for ABL profiling and investigations of turbulence parameters as part of a Polarstern cruise in the Antarctic Weddell-Sea during polar night between 8 June and 12 August 2013. Eleven research flights were carried out with the M2AV but the field activity was strongly affected by a multitude of critical challenges like icing, strong wind speed and externally driven limitations, mainly influenced by the need of a suitable airfield on sea ice. The results address a ... : In dieser Dissertation werden mit Hilfe von unbemannten Forschungsflugzeugen dynamische Prozesse und Aerosolpartikel innerhalb der atmosphärischen Grenzschicht (AGS) an zwei unterschiedlichen Messstandorten (Polargebiet und kontinentaler Raum in Mitteleuropa) untersucht. Der Einsatz von unbemannten Flugsystemen liefert einen erheblichen Beitrag zu aktuell bestehenden Datenlücken, die auf Grund fehlender Messmethoden im kleinskaligen Raum innerhalb der AGS existieren. Das unbemannte Forschungsflugzeug vom Typ Carolo T200 ”M2AV” (Mini Meteorological Aerial Vehicle) wurde auf einer Polarstern- Forschungsfahrt im antarktischen Weddellmeer, unter dem Einfluss der Polarnacht, eingesetzt. Im zwölfwöchigen Zeitraum vom 8. Juni bis 12. August 2013 wurden elf Messflüge durchgeführt, wobei der Feldeinsatz durch die Gegebenheiten vor Ort stark eingeschränkt wurde, wie zum Beispiel häufiges Auftreten von starken Winden, Vereisung und äußeren Einschränkungen, welche unter anderem der Bedingung einer geeigneten Startbahn ...